Shank3 deficiency elicits autistic-like behaviors by activating p38α in hypothalamic AgRP neurons - Shanshan Wu; Jing Wang; Zicheng Zhang; Xinchen Jin; Yang Xu; Youwen Si; Yixiao Liang; Yueping Ge; Huidong Zhan; Li peng; Wenkai Bi; Dandan Luo; et al. (Molecular Autism, 2024)
Abstract Background SH3 and multiple ankyrin repeat domains protein 3 (SHANK3) monogenic mutations or deficiency leads to excessive stereotypic behavior and impaired sociability, which frequently occur in autism cases. To date, the underlying mechanisms by which Shank3 mutation or deletion causes autism and the part of the brain in which Shank3 mutation leads to the autistic phenotypes are understudied. The hypothalamus is associated with stereotypic behavior and sociability. p38α, a mediator of inflammatory responses in the brain, has been postulated as a potential gene for certain cases of autism occurrence. However, it is unclear whether hypothalamus and p38α are involved in the development of autism caused by Shank3 mutations or deficiency. Methods Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis and immunoblotting were used to assess alternated signaling pathways in the hypothalamus of Shank3 knockout (Shank3 −/− ) mice. Home-Cage real-time monitoring test was performed to record stereotypic behavior and three-chamber test was used to monitor the sociability of mice. Adeno-associated viruses 9 (AAV9) were used to express p38α in the arcuate nucleus (ARC) or agouti-related peptide (AgRP) neurons. D176A and F327S mutations expressed constitutively active p38α. T180A and Y182F mutations expressed inactive p38α. Results We found that Shank3 controls stereotypic behavior and sociability by regulating p38α activity in AgRP neurons. Phosphorylated p38 level in hypothalamus is significantly enhanced in Shank3 −/−  mice. Consistently, overexpression of p38α in ARC or AgRP neurons elicits excessive stereotypic behavior and impairs sociability in wild-type (WT) mice. Notably, activated p38α in AgRP neurons increases stereotypic behavior and impairs sociability. Conversely, inactivated p38α in AgRP neurons significantly ameliorates autistic behaviors of Shank3 −/− mice. In contrast, activated p38α in pro-opiomelanocortin (POMC) neurons does not affect stereotypic behavior and sociability in mice. Limitations We demonstrated that SHANK3 regulates the phosphorylated p38 level in the hypothalamus and inactivated p38α in AgRP neurons significantly ameliorates autistic behaviors of Shank3 −/− mice. However, we did not clarify the biochemical mechanism of SHANK3 inhibiting p38α in AgRP neurons. Conclusions These results demonstrate that the Shank3 deficiency caused autistic-like behaviors by activating p38α signaling in AgRP neurons, suggesting that p38α signaling in AgRP neurons is a potential therapeutic target for Shank3 mutant-related autism.